Better call Saul. [videorecording (DVD)] Season two. - Banks, Jonathan, 1947-; Gilligan, Vince; Seehorn, Rhea, 1972- (Sony Pictures Home Entertainment, 2016)
The trials and tribulations of criminal lawyer, Jimmy McGill, leading up to establishing his strip-mall law office in Albuquerque, New Mexico.